KOMUNIKASI DALAM MENERTIBKAN ANGKUTAN UMUM PENUMPANG ILLEGAL TAHUN 2011-2013 DI KABUPATEN KUANTAN SINGINGI - Imron Rosyadi; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Supervision of the Department of Transportation and CommunicationInformation in Public Transport Passenger curb Illegal Year 2011-2013 inKuantan Singingi District.Informants in this study were Apparatus Information and CommunicationDepartment of Transportation, Traffic Police Unit officers Regency KuantanResort Singingi, and the owner of freight or passenger public transport driversillegal, based on the type of four-wheeled vehicles that rode in Kuantan SingingiDistrict, which is determined by purposive according to research needs.This study aims to determine the cause of the Transport Department ofInformation and Communications is not able to regulate the public transport ofpassengers Illegal Year 2011-2013 in Kuantan Singingi District. In this study,researchers used qualitative methods to analyze the data is descriptive analysis.Data collection techniques in this study is the observation and interview, whiledata analysis technique that is use qualitative analysis, by analyzing theexpression or records available or observed behavior. Qualitative analysis wasperformed on the data, in this case the qualitative data in the form of information,a description in the form of prose language, then linked with other data to obtainclarity on the truth.Conclusions from the study regarding the supervision of Department ofTransportation and Communications in Information Public transport passengercurb Illegal Year 2011-2013 In Singingi Regency Kuantan is still less than themaximum , because they have not been able to curb illegal entire public transportpassengers in Kuantan Singingi District are caused by several factors in amongthese are the lack of rigor officer at the time of supervision and lack of firmnesssanctions applied so as not to make the driver feel afraid or transit abundant inaction, as well as lack of awareness of the driver and the passenger transportillegal.Keywords: Monitoring, Control and Demolition.